Práticas de instrução fônica em alunos do 2º, 3º e 4º anos com dificuldades na aprendizagem da linguagem escrita - Peçanha, Célia Regina Ferreira (2020)
This study adresses the benefits of phonics for dealing with difficulties in literacy. The study assumes that the learning process focused on phonics instruction in the early stages of literacy correlates positively in the learning process of the writing and reading skills. The study poses two main questions: What are the effects of a phonics instruction program on students with serious literacy gaps in their early grades? What is the relation between phonological awareness and literacy in students attending 2nd to 4th grades of elementary school? The main objective was to evaluate the contribuition of an intervention guided by phonics instruction through writing and phonological awareness, in the development of students who present a delay in their early learning stages. The specific objectives were: assess the progress of those students in their writing and reading learning process, check whether the intervention process also adresses the needs of children with language problems, and relate phonological awareness to those children’s literacy learning process. The study is justified by the importance of conducting interventions based on scientific evidences in literacy, so that students can not only improve their writing learning process but also remain motivated to continue with their studies. The theoretical grounds of this study follow the Cognitive Psychology of Reading principles, based on one of its metalinguistic skills, the phonological awareness. The participants were six students attending the 2nd, 3rd and 4th grades of an elementary school located in the countryside of São Paulo state. The study comprises three stages: pre-test, intervention and post-test, with written language assessments and phonological awareness from the beginning to the end of the intervention. The results confirm the benefits of phonological awareness in students with serious gaps in reading and writing during the literacy stage